El hule: de los olmecas a los polímeros sintéticos - Vázquez Moreno, Flavio; Cruz Almanza, Raymundo; Ángeles Anguiano, Enrique; Olea Cardoso, Óscar; López Castañares, Rafael (CIENCIA ergo-sum; Vol. 5 Núm. 1 (1998): CIENCIA ergo-sum (marzo-junio 1998), 2017)
-